Protection of the house against Chagas disease, dengue, leishmaniasis, and lymphatic filariasis: a systematic review. Issue 5 (May 2018) - Horstick, Olaf; Runge-Ranzinger, Silvia
Summary: In light of the recent Zika virus outbreak, vector control has received renewed interest. However, which interventions are efficacious and community effective and how to best deliver them remains unclear. Following PRISMA guidelines, we did a systematic review to assess evidence for applied vector control interventions providing protection against Chagas disease, dengue, leishmaniasis, and lymphatic filariasis at the household level. We searched for published literature and grey literature between Jan 1, 1980, and Nov 30, 2015, and updated our search on April 2, 2017, using databases including the Cochrane, Embase, LILACS, PubMed, Web of Science, and WHOLIS. The Cochrane Collaboration's tool for assessing risk of bias was used. Inclusion criteria included studies reporting vector control interventions in and around a house or dwelling; and use of insecticides as sprays on netting or screens, and any method to control larval breeding in water containers in and around the home. 1416 articles were assessed and 32 articles included. The most effective interventions affecting vector indices for multiple diseases were found to be intradomiciliary residual spraying, insecticide-treated materials (especially insecticide-treated nets or curtains), and treatment of larval habitats with biological and chemical methods. Waste management and clean-up campaigns reduce vector populations, although to a lesser extent than other interventions and not consistently. Modifications to the structure of homes (eg, wall plastering) had no impact on the control of vectors. Protection of the house and its surroundings might affect the transmission of several diseases. The most effective interventions should be prioritised when vector control programmes are designed; however, the quality of delivery (ie, coverage and reapplication) of interventions is a crucial factor to ensure their effectiveness. Additional randomised trials that assess the measures of human disease and eventually target several diseases with a combination of interventions that protect the household and its inhabitants against multiple vectors, are needed to inform global policy in this area.